Abundance of soil invertebrates in differently-managed land in relation to soil physicochemical parameters - Hamzah, Nurul Hazirah (2019)
The soil biota is considered as the biological engine of the earth and is associated in most of the critical functions of the soil in terms of ecosystem services. The knowledge on the impact of land management and agricultural activities on the abundance and diversity of soil invertebrates is still understudied especially in Malaysia. This study was conducted to investigate the soil-physico-chemical parameters from differently managed land around UPM. Next, is to measure the abundance and diversity of macro and microinvertebrates in differently managed land around UPM. Lastly is to obtain the relation between invertebrates’ abundance with soil parameters. Sampling methods of soil invertebrates include pitfall trap and Burlese-Tullgren funnel. Invertebrate’s abundance and diversity was measured and invertebrates were identified according to their morphological characteristics under the dissecting microscope with reference to taxonomic keys. Invertebrates were classified according to morphospecies and size which were macroinvertebrates and microinvertebrates. Additionally, the basic soil physical properties were also analysed using the rank-based method. A total of 5849 individuals were collected from 28 soil invertebrates’ orders. Hymenoptera (83.93%) is the most dominant macroinvertebrates followed by Amphypoda (51.15%) and Orthoptera (13.62%). Hymenoptera is also the dominant microinvertebrates recorded (75.28%) followed by Acarina (52.59%) and Coleoptera (13.64%). Morphospecies diversity is the highest in durian farm (Shannon; 1.54) while, morphospecies evenness is the highest in vegetable farm (Evenness; 0.32) and morphospecies richness is highest in pasture land (Menhinick; 0.67). Reduced agricultural activities in durian farm, which recorded ideal soil physical parameters (soil porosity; 55.11 % ± 0.13 and soil temperature; 32.58 ⁰C ± 0.16) produces a comparatively more balanced habitat for a diverse community of soil invertebrates. CCA results suggest that soil moisture, soil temperature and soil EC are vital elements in the influence of soil invertebrate’s abundance. Because of the roles they play in soil biological processes, soil invertebrates may be used as bioindicators of soil health. This study can be used as a baseline for a more extensive research that may be applied in future planning on land management in achieving the nation’s agricultural sustainability.